Gold(I)-catalyzed intermolecular hydroalkoxylation of allenes: a DFT study. - Paton, R; Maseras, F (2009)
The mechanistic and regiochemical aspects in the Au(I)-catalyzed intermolecular hydroalkoxylation of allenes have been studied computationally. The most favorable pathway is nucleophilic attack of an Au(I)-coordinated allene, which occurs irreversibly. An Au(I)-catalyzed mechanism is proposed that allows the facile interconversion of regioisomeric allylic ether products. The regioisomers are connected via a stabilized diether intermediate with a C-Au sigma-bond, which successfully explains the observed regioselectivity for the thermodynamic product.